Development of a prognostic model based on immunogenic cell death/ferroptosis-related genes and the study of TREX1 effects on prostate cancer cells - Wen, Yaoan; Zhan, Shuyuan; Chen, Jianhui; Yang, Jiangbin; Chen, Dandong; Zheng, Song; Zhu, Shaoxing (Frontiers in Immunology, 2025)
BackgroundUnderstanding the interplay between immunogenic cell death (ICD), ferroptosis, and prostate cancer (PCa) is critical for elucidating the underlying mechanisms of PCa pathogenesis. This study aimed to establish a prognostic model for PCa based on ICD- and ferroptosis-related genes (IFRGs) and to evaluate its potential clinical applicability.MethodsRNA sequencing data and clinical information of PCa patients were obtained from The Cancer Genome Atlas (TCGA-PRAD) database. Candidate IFRGs were identified through Pearson correlation and differential expression analyses. A prognostic model was constructed using univariate Cox regression, least absolute shrinkage and selection operator (LASSO) regression, and Kaplan–Meier survival analyses, and subsequently validated in an external cohort (GSE70769). In addition, siRNA-mediated knockdown of the key gene TREX1 was performed in PC-3 cells, and EdU and Transwell assays were conducted to assess its effects on tumor cell proliferation, migration, and invasion.ResultsA three-gene IFRG-based prognostic model was developed, which effectively stratified PCa patients into high- and low-risk groups with significantly different survival outcomes. Multivariate Cox regression analysis confirmed the model as an independent prognostic factor. Functional experiments further demonstrated that TREX1 serves as a critical risk gene, and its knockdown markedly suppressed the proliferative, migratory, and invasive capacities of PCa cells.ConclusionThe three-gene IFRG-based prognostic model may serve as a promising prognostic biomarker for PCa, providing predictive value and novel insights into the complex interactions between IFRGs and PCa progression. Moreover, TREX1 was identified as a potential therapeutic target, offering new perspectives for prognostic assessment and the development of immunotherapy strategies in PCa.